NETWORK DESIGN PRINCIPLES FROM THE SEA URCHIN EMBRYO - Davidson, Eric H. (2009)
As gene regulatory network models encompass more and more of the specification processes underlying sea urchin embryonic development, topological themes emerge that imply the existence of structural network “building blocks”. These are subcircuits which perform given logic operations in the spatial control of gene expression. The various parts of the sea urchin gene regulatory networks offer instances of the same subcircuit topologies accomplishing the same developmental logic functions but using different genes. These subcircuits are dedicated to specific developmental functions, unlike simpler “motifs”, and may indicate a repertoire of specific devices of which developmental gene regulatory networks are composed.